Penguatan Penyusunan Modul Projek Profil Pelajar Pancasila Pada Sekolah Penggerak Jenjang SMA - Wijayanti, Palupi Sri; Jamilah, Fitri; Herawati, Tri Ratna; Kusumaningrum, Rika Novita (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Learning at the driving school requires the existence of project activities where the project aims to provide character strengthening for students with a Pancasila student profile. The project must be designed as creatively as possible in order to provide a very good experience for students so that it is necessary to strengthen the preparation of the Pancasila student profile project module. This service activity is carried out in three stages, namely preparation, implementation, and evaluation. Preparation is carried out by providing materials as references and guidelines in the development of the Pancasila student profile project module. In addition, it also documents licensing and adjustments to the schedule for the implementation of service. In the second stage, service is carried out by providing school-level measurement instruments then delivering material and criticizing existing project modules. At the evaluation stage, it is done by reflecting on all participants on the activities that have been carried out. The results of the activity show that high school teachers can develop a Pancasila student profile project module and can conduct an assessment in accordance with the reference guidelines for strengthening the Pancasila student profile project.